The scarecrow - Ferry, Beth; Fan Brothers (New York: Harper, 2019)
All the animals know not to mess with old Scarecrow. But when a small, scared crow falls from midair, Scarecrow does the strangest thing. He saves the tiny baby crow. Soon a loving bond grows between the two unlikely friends. But is it strong enough to weather the changing of the seasons?
Publishers Weekly, May 2019
Kirkus Review, June 2019
2.0
K-3
AD490L
Keywords: Animals -- Juvenile fiction; Friendship -- Juvenile fiction; Seasons -- Juvenile fiction; Animals -- Fiction; Friendship -- Fiction; Seasons -- Fiction; Picture books